The impact of neighborhood mental health on the mental health of older adults - Rengui Gong; Dongping Xia; Zan Hu; Yangming Hu (BMC, 2023)
Abstract Background In this article, we use cross-sectional data obtained from the 2018 China Health and Aging Tracking Survey (CHARLS) to examine the impact of neighborhood mental health at the community level on the mental health of older adults aged 60 years and older. Methods NMH is the average mental health of older adults in the same community, excluding the older adults themselves. The explained variable mental health in this paper was measured using the simple CES-D depression scale. The mediating variables were social connectedness, social participation and social inclusion, and the instrumental variables were physical exercise and amusement. regression analysis was conducted using OLS regression models, two-stage least squares (IV-2SLS) instrumental variables to address the two-way causality of NMH and MH, and KHB decomposition was used to investigate the effect mechanism. Results Baseline regressions showed that the neighborhood mental health effect positively influenced the mental health of older adults (Coef. = 0.356, 95% CI 0.315,0.397). The neighborhood mental health effect estimated by IV-2SLS (Coef. = 0.251, 95% CI 0.096,0.405) was higher than the OLS regression, indicating endogeneity. The mediated effects of KHB showed total (Coef. = 0.356, 95% CI 0.314,0.398), direct (Coef. = 0.281, 95% CI 0.232,0.330), and indirect effects (Coef. = 0.075, 95% CI 0.049,0.101). While the total effect was 1.266 times higher than the direct effect, 21.03% of the total effect came from mediating variables. Conclusions First, the neighborhood mental health effect has a positive impact on the mental health of older adults, but there are heterogeneous differences based on gender, age, and place of residence. Second, the results of the IV-2SLS estimation showed that the effect of the neighborhood mental health effect was underestimated if endogenous problems were not controlled for. Third, the effect of neighborhood mental health on older adults' mental health was tested to be stable. Moreover, social connectedness, social participation, and social interaction are important mediating mechanisms for the effect of neighborhood mental health on older adults' mental health. This study provides new perspectives and ideas for an in-depth understanding of the mental health of older adults in the context of social transformation in China.